Osmotic pretreatment for the production of novel dehydrated tomatoes and cucumbers. Issue 7 (29th April 2019) - Dermesonlouoglou, Efimia K.; Pantelaiaki, Kallirroi; Andreou, Varvara; Katsaros, George J.; Taoukis, Petros S.
Abstract: The aim of this study was the implementation of osmotic dehydration (OD) as a pre‐drying step for producing novel dried tomatoes and cucumbers. Tomato and cucumber slices were immersed in glycerol ( Cgly :50–60%w/w), maltodextrin, trehalose, sodium chloride, calcium chloride, and citrus extract solution ( TOD :35–55°C) and air‐dried (AD, TAD :40–70°C). The mass transfer (water and solids) and water activity reduction were monitored during OD. The effective diffusion coefficients for water and solids ( Dew, OD/ Des, OD, ) were calculated and modeled. The effective diffusion coefficients for water and water removal rate constants during AD ( Dew, AD, kdrying ) were calculated and modeled. The drying times were estimated. The rates were significantly greater for osmotically dehydrated tomatoes and cucumbers compared to the non‐dehydrated ones. Drying times significantly reduced for the osmotically dehydrated samples. Comparing tomato and cucumber response to OD, it was concluded that osmotic dehydration favors cucumber water loss and tomato solid uptake. Dew, OD/ Des, OD and Dew, AD /kdrying were significantly higher for cucumber than tomato. Practical applications: Air‐drying is a food preservation technique with long processing times and high energy costs. The application of osmotic dehydration as a pre‐drying step can significantly reduce drying times and temperatures, resulting in lower energy requirements as well as improved quality and increased shelf life. Osmotic dehydration led to water transfer from food material (usually fruit and vegetable) to osmotic solution and osmotic solutes' transfer to food material. It is commonly applied at mild temperatures as a pre‐processing step. More recently, the efforts have been on the selection of alternative osmotic solutes (such as glycerol, and other solutes with special properties) and their use in the osmotic solution which will be effective and provide better nutritional, functional or sensorial properties to the osmo‐dehydrated food material. An interesting proposal is to produce dehydrated (sliced) tomato and (especially) cucumber products of high quality and increased shelf life, applying osmotic dehydration, and air‐drying.